Cardiopulmonary effects of anaesthesia maintained by propofol infusion versus isoflurane inhalation in cheetah (Acinonyx jubatus) - Zeiler, Gareth Edward (University of Pretoria, 2018)
Dissertation (MMEDVET)--University of Pretoria, 2017.